Pengembangan Kompetensi Nazhir Menuju Wakaf yang Berdaya - Danial Kusumah (La Zhulma | Jurnal Ekonomi dan Bisnis Islam, 2023)
The stagnation of waqf assets in Indonesia can hinder the achievement of the objective of waqf existence itself, which is to develop the potential and economic benefits of waqf assets to improve people's welfare. This study aims to examine solutive instruments to improve nazhir competence in order to obtain added value for the management and development of waqf assets. Researchers use documentation studies to collect information in the form of books, journal articles, reports, regulations, and other documents related to waqf. The results of the study concluded that in order to increase nazhir competence in running productive waqf, nazirs should master the technique of preparing a business feasibility study. The ability to compile business feasibility scientifically accompanied by an analysis of the implementation of sharia principles is expected to be able to formulate a productive waqf program design that is comprehensive, measurable, scientific, has beneficial value, and has leverage on the added value of waqf assets